Eating habits of students during a typical exam period-Case of Kosovo - Salihu, Salih; Gashi, Njomza (International Journal of Public Health Science (IJPHS), 2024)
The exam period is a stressful period for students, which often influences them to make wrong food choices. This study examines the eating habits of students during a typical exam period, to understand their food patterns or dietary choices, in a period when they have greater stress due to the high academic demands at the university. The 200 students of different academic levels at the University of Prishtina participated in this research. Data have been compiled through online questionnaires where the respondents were asked to anonymously declare their health status, the number of meals they take per day during a typical exam period, their food preferences, physical activity, and sleep. Results showed that Kosovar students have unhealthy eating habits during exam periods. They have a disorder in the time and number of meals they take during the day on a typical exam period, compared to other periods of the year. The findings of this research contribute to the existing literature related to dietary habits of students in stressful periods, providing knowledge for students and addressing the issue of education for healthy nutrition in educational institutions.